Rationality and Relationality in the Process of Whistleblowing: Recasting Whistleblowing Through Readings of Antigone. (October 2014) - Contu, Alessia
Reporting wrongdoing is seen as desirable to fight illegal practices, but whistleblowers often suffer retaliations and are in need of protection. Overall, whistleblowers engender strong reactions and are cast either as saints or rats. I consider why whistleblowers are seen as unsettling and ambivalent figures by exploring the analogy between Antigone, the Sophoclean heroine, and whistleblowers. These reflections reconfigure the rationality and relationality of the process of whistleblowing. The rationality of the whistleblower is singular and not easily subsumed into universalizing norms which explains some of the limits reached by the empiricist pro-social research agenda. The relationality of the process of whistleblowing indicates that the reactions of those who hear the whistle are as important. This opens up to an appreciation of the ethical and political valence of the process of whistleblowing and highlights a number of counter-intuitive and interesting issues in its synchronic and diachronic dimension.